PERANAN ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA SMP DI DESA MALO JELAYAN KABUPATEN BENGKAYANG - Ita Riana; Junaidi H. Matsum; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The purpose of this research was to found out the role of parents in motivating junior high school students' learning at Desa Malo Jelayan Bengkayang. The research problems were: 1) how did the parents' role in motivating junior high school students at Desa Malo Jelayan Bengkayang from the view of providing education; 2) how did the parents' role in motivating junior high school students at Desa Malo Jelayan Bengkayang from the view of practicing patience; 3) how did the parents' role in motivating junior high school students at Desa Malo Jelayan Bengkayang from the view of knowing students' difficulties in learning; 4) how did the parents' role in motivating junior high school students at Desa Malo Jelayan Bengkayang from the view of providing learning facilities. The method used was qualitative descriptive. The source of the data was five parents. The research tools were observation guideline, interviews, and documentation. The result showed that the parents' role in motivating students from the view of providing education was poor, parents' role from the view of practicing patience was good, parents' role from the view of knowing students' difficulties in learning was excellent, parents' role from the view of  providing learning activities was poor. Keywords: Parents' Role, Motivation, Learning